2016
DOI: 10.1021/acs.est.5b04694
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Solution Chemistry and Soft Protein Coronas on the Interactions of Silver Nanoparticles with Model Biological Membranes

Abstract: The influence of solution chemistry and soft protein coronas on the interactions between citrate-coated silver nanoparticles (AgNPs) and model biological membranes was investigated by assembling supported lipid bilayers (SLBs) composed of zwitterionic 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) on silica crystal sensors in a quartz crystal microbalance with dissipation monitoring (QCM-D). Our results show that the deposition rates of AgNPs on unmodified silica surfaces increased with increasing electrolyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 66 publications
(137 reference statements)
2
28
0
Order By: Relevance
“…When proteins cover the surface of the AgNPs, forming what is known as a biocorona, this decides the fate of the AgNPs in vivo. [8][9][10][11] Sharma and coworkers reviewed the effects of the coating on AgNPs on the fate, stability and toxicity of the AgNPs in aqueous solutions and biological systems. 12 It was shown that the key factors contributing to the fate and toxicity of AgNPs are the size, shape, surface coating, surface charge and conditions of silver ion release, which provide some new insight into understanding the biological impact of AgNPs on humans and organisms.…”
Section: Introductionmentioning
confidence: 99%
“…When proteins cover the surface of the AgNPs, forming what is known as a biocorona, this decides the fate of the AgNPs in vivo. [8][9][10][11] Sharma and coworkers reviewed the effects of the coating on AgNPs on the fate, stability and toxicity of the AgNPs in aqueous solutions and biological systems. 12 It was shown that the key factors contributing to the fate and toxicity of AgNPs are the size, shape, surface coating, surface charge and conditions of silver ion release, which provide some new insight into understanding the biological impact of AgNPs on humans and organisms.…”
Section: Introductionmentioning
confidence: 99%
“…In these surface-based systems, nanostructured surfaces such as nanodisks and nanoholes may be utilized as underlying substrates, which have consequently prompted studies on the interaction between nanostructured surfaces and lipid bilayers [ 75 , 76 , 77 , 78 ]. Well-characterized bilayer coatings have been employed to study lipid bilayer interactions with biomacromolecules [ 79 , 80 , 81 ] as well as with native [ 82 , 83 , 84 ] and functionalized nanoparticles [ 85 , 86 , 87 , 88 , 89 ] with consideration of various parameters such as nanoparticle size as well as surface property variations (e.g., charge, hydrophobicity) of both the nanoparticles and lipid bilayers. On a related note, some of these studies have been conducted using advanced label-free optical sensing techniques such as optical waveguide spectroscopy [ 80 ] and waveguide total internal reflection microscopy [ 85 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, based on Le Bihan et al (2009), our AgNPs with a size less than or equal to 5 nm would not possess sufficient adhesion strength to cause invagination and could only adsorb to the surface of the liposomes. Moreover, considering the small amounts of silver found associated with the liposomes (on average 38.3 ÎŒmol Ag / g P, corrected for the residual amount of Ag), we can hypothesize that the invagination of silver nanoparticles is unlikely and that AgNPs only adsorbed to the surface of the liposomes, as has been shown by Wang et al (2016).…”
Section: Discussionmentioning
confidence: 59%